1988
DOI: 10.1002/mus.880110706
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucocorticoids on motor units in cat hindlimb muscles

Abstract: The purpose of this study was to examine the effects of glucocorticoid treatment on the contractile, electrical and fatigue properties of isolated motor units of identified type. Although it is known that glucocorticoid administration induces atrophy and weakness most strongly in fast, pale muscles and to a lesser extent in red muscle, the relationship between steroid effects and motor unit type is not known. Properties of medial gastrocnemius (MG) and soleus (SOL) motor units were studied in normal cats and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Muscle breakdown leads to wasting and weakness, which is often obvious to owners (Robinson and Clamann, 1988). Cortisol causes protein catabolism and, thus, breakdown of muscle.…”
Section: Weakness Lethargy Potbelly and Bruisingmentioning
confidence: 99%
“…Muscle breakdown leads to wasting and weakness, which is often obvious to owners (Robinson and Clamann, 1988). Cortisol causes protein catabolism and, thus, breakdown of muscle.…”
Section: Weakness Lethargy Potbelly and Bruisingmentioning
confidence: 99%
“…However, experimental work on the effects of glucocorticoids on isolated feline motor units suggested that weakness occurred preferentially in fast-twitch motor units, primarily as a result of reduction in contractile protein. 20 The diagnosis of congenital myotonia was made in the cats of this report based on the age of onset, historical information, physical examination findings, the absence of evidence of progressive or inflammatory disease, provocative testing to rule out endocrinopathies, production of a myotonic dimple (1 cat), and classical electrodiagnostic findings. Because the age of onset and profound muscular enlargement made feline muscular dystrophy the most likely differential diagnosis other than myotonia, it is worth reiterating the fact that serum activities for muscle-associated enzymes were normal and that 1 of the affected cats is a female.…”
Section: Overview and Pathophysiologymentioning
confidence: 99%
“…Nonsteroidal antiinflammatory drugs are often used in the clinical setting, although data regarding their short-and longterm benefits are conflicting. 6,20,24 Despite the fact that corticosteroids have repeatedly been shown to be catabolic and inhibit the healing process, 8,9,13,20,23,[25][26][27][31][32][33] they continue to be used clinically to treat muscle contusion injuries and are injected into the site of injury to relieve pain and expedite a player's return to active status.…”
mentioning
confidence: 99%